2020
DOI: 10.1113/ep087770
|View full text |Cite
|
Sign up to set email alerts
|

Connexin‐mediated cell communication in the kidney: A potential therapeutic target for future intervention of diabetic kidney disease?

Abstract: The ability of cells to communicate and synchronise their activity is essential for the maintenance of tissue structure, integrity and function. A family of membrane-bound proteins called connexins are largely responsible for mediating the local transfer of information between cells. Assembled in the cell membrane as a hexameric connexon, they either function as a conduit for paracrine signalling, forming a transmembrane hemi-channel, or, if aligned with connexons on neighbouring cells, form a continuous aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 116 publications
(142 reference statements)
0
8
0
2
Order By: Relevance
“…Hyperglycemia and downstream changes in connexin expression are critical in the development and progression of secondary micro-vascular complications, [12][13][14][15] with glucose decreasing gap junction conductance and disrupting cellular homeostasis in a variety of cell types [16][17][18][19]. Evidence that connexin expression is linked to renal damage in CKD [9,11,12,[20][21][22][23][24], suggests that they represent a viable therapeutic target for treatment of the disease. Recent studies have confirmed elevated levels of predominant isoform Cx43, in human and rodent models of early renal disease [20,21] whilst the Cx43 +/− unilateral ureteral obstruction (UUO) mouse demonstrates reduced collagen deposition and macrophage infiltration [24].…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia and downstream changes in connexin expression are critical in the development and progression of secondary micro-vascular complications, [12][13][14][15] with glucose decreasing gap junction conductance and disrupting cellular homeostasis in a variety of cell types [16][17][18][19]. Evidence that connexin expression is linked to renal damage in CKD [9,11,12,[20][21][22][23][24], suggests that they represent a viable therapeutic target for treatment of the disease. Recent studies have confirmed elevated levels of predominant isoform Cx43, in human and rodent models of early renal disease [20,21] whilst the Cx43 +/− unilateral ureteral obstruction (UUO) mouse demonstrates reduced collagen deposition and macrophage infiltration [24].…”
Section: Introductionmentioning
confidence: 99%
“…Connexin hemichannel blockers represent a promising future therapeutic option in the treatment of nephropathy and retinopathy. Research to date is persuasive and highlights promising beneficial effects of Cx43 inhibition on inflammation, tissue integrity and fibrosis [ 180 , 201 , 202 ]. However, the field requires further research to determine the effectiveness and efficacy of drugs and the long-term benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Intercellular communication in the kidney occurs directly via the cytoplasm of adjacent cells connected through GJs, and by paracrine signals released via large-pore channels, such as HCs, pannexons and P2X 7 Rs [ 72 ]. The release of ATP via HCs has multiple functions in the kidney, including regulating renal blood flow, glomerular filtration rate, and renal tubular transport [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The release of ATP via HCs has multiple functions in the kidney, including regulating renal blood flow, glomerular filtration rate, and renal tubular transport [ 73 ]. However, the HC-mediated release of ATP and further activation of P2 × 7 Rs have been linked to inflammation and fibrosis [ 72 , 74 ]. Multiple studies argue that proinflammatory cytokines may contribute to a chronic activation of endothelial cells, and thereby, a long-term production of key “danger” signals, such as ATP [ 20 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%